Multiple prior concussions are associated with symptoms in high school athletes. (3rd June 2014) - Mannix, Rebekah; Iverson, Grant L.; Maxwell, Bruce; Atkins, Joseph E.; Zafonte, Ross; Berkner, Paul D.
Abstract Objectives The purpose of this study was to evaluate the association of prior concussion on baseline computerized neurocognitive testing in a large cohort of high school athletes. Methods This is a retrospective cohort study of student athletes from 49 Maine High Schools in 2010 who underwent baseline computerized neurocognitive evaluation with Immediate Post‐Concussion Assessment and Cognitive Testing (ImPACT®). As part of the ImPACT®, subjects reported a prior history of concussion as well as demographic information and a symptom questionnaire. We used linear regression to evaluate the association of prior concussion with baseline: (1) ImPACT® composite scores; and (2) symptom scores. Results Six thousand seventy‐five subjects were included in the study, of whom 57% were boys. The majority of student athletes (85.3%) reported no prior history of concussion while 4.6% reported having sustained two or more prior concussions. On simple linear regression, increasing number of concussions was related to worse performance in verbal memory (P = 0.039) and greater symptoms scores (P < 0.001). On multivariate modeling, only the association with baseline symptoms remained (P < 0.001). Other factors associated with baseline symptom reporting in the multivariate model included mental health history, headache/migraine history, gender, developmental and/or learning problems, and number of prior concussions. Interpretation In this large‐scale, retrospective survey study, history of multiple prior concussions was associated with higher symptom burden but not baseline computerized neurocognitive testing. The association between baseline symptom reporting and clinical and demographic factors was greater than the association with a history of multiple concussions.